Corrigendum: Warriors and Weavers: The Poetics and Politics of Indigenous Appropriations of New Media Technologies in Latin America. Issue 1 (22nd October 2021) - Pitman, Thea
Following the publication of our article in Modern Languages Open ( http://doi.org/10.3828/mlo.v0i0.207 ) we wish to bring the following corrigendum to your attention.